2019
DOI: 10.3390/agriculture9070136
|View full text |Cite
|
Sign up to set email alerts
|

Effect of GA3 and Gly Plant Growth Regulators on Productivity and Sugar Content of Sugarcane

Abstract: The use of plant growth regulators is one effective solution to improve sugarcane yields and sugar content in several countries. In this study, we examined the role of gibberellin acid (GA3) and glyphosate (Gly) plant growth regulators to determine the appropriate concentration of GA3 and Gly to increase the yield of sugarcane and sugar accumulation, respectively. The statistical results showed that GA3 was sprayed at 150 ppm to increment the actual yield by 19.94%; sucrose accumulation increased by 2.21%. Wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 28 publications
0
6
0
2
Order By: Relevance
“…The results showed that GA3 treatment produced bulbils with the highest weight and diameter (Table 2). This is because GA3 plays a role in sucrose phosphosynthase activity, one of the main enzymes involved in sucrose synthesis and promotes tissue proliferation, which leads to a better assimilation process (Nguyen et al, 2019). The number of bulbils formed, weight and diameter of bulbils in GA3 treatment was not significantly different from the wound treatment of flower stalks.…”
Section: Initiation Of Flowering and Bulbils In Shallot With Various ...mentioning
confidence: 97%
“…The results showed that GA3 treatment produced bulbils with the highest weight and diameter (Table 2). This is because GA3 plays a role in sucrose phosphosynthase activity, one of the main enzymes involved in sucrose synthesis and promotes tissue proliferation, which leads to a better assimilation process (Nguyen et al, 2019). The number of bulbils formed, weight and diameter of bulbils in GA3 treatment was not significantly different from the wound treatment of flower stalks.…”
Section: Initiation Of Flowering and Bulbils In Shallot With Various ...mentioning
confidence: 97%
“…Penggunaan ZPT di bidang pertanian dapat memberikan kontribusi besar dalam peningkatan pertumbuhan, produksi, dan kualitas tanaman tebu (Patel & Chaudhary, 2018). Penggunan ZPT pada pertanaman tebu juga mampu meningkatan jumlah akumulasi sukrosa, produktivitas dan juga keuntungan bagi petani tebu (Nguyen, Dang, Nguyen, & Tran, 2019). Salah satu ZPT yang telah banyak dikenal yaitu Atonik yang memiliki kandungan natrium para-nitrofenolat PNP (0,3%), natrium orto-nitrofenolat ONP (0,2%) dan natrium 5-nitroguaiacolate 5NG (0,1%) (Kociraa et al, 2017) yang mampu meningkatkan pertumbuhan vegetatif dan produksi (Banful & Attivor, 2017).…”
Section: Pendahuluanunclassified
“…Copolymer solution with predetermined Glu/Arg concentration was lyophilized for further use in Glu/Arg content evaluation and in vitro release behavior. Since it is difficult to determine the content of Glu/ Arg loaded CS-P407 hydrogels, a mediated-reagent (FMOC-Cl) was used to quantify different amino acids via reactions between amino acids and FMOC-Cl [18][19][20]. Pure Glu/Arg was dissolved in H 2 O with various concentrations (in the range from 1 to 10 ppm).…”
Section: Cs-p407 Hydrogel Containing Amino Acidmentioning
confidence: 99%